Augmented and Virtual Reality Instrument Tracking for Minimally Invasive Spine Surgery: A Feasibility and Accuracy Study. Issue 15 (1st August 2019) - Burström, Gustav; Nachabe, Rami; Persson, Oscar; Edström, Erik; Elmi Terander, Adrian
Abstract : Study Design: Cadaveric animal laboratory study. Objective: To evaluate the feasibility and accuracy of pedicle cannulation using an augmented reality surgical navigation (ARSN) system with automatic instrument tracking, yielding feedback of instrument position in relation to deep anatomy. Summary of Background Data: Minimally invasive spine surgery (MISS) has the possibility of reducing surgical exposure resulting in shorter hospital stays, lower blood loss and infection rates compared with open surgery but the drawback of limiting visual feedback to the surgeon regarding deep anatomy. MISS is mainly performed using image-guided 2D fluoroscopy, thus exposing the staff to ionizing radiation. Methods: A hybrid operating room (OR) equipped with a robotic C-arm with integrated optical cameras for augmented reality instrument navigation was used. In two pig cadavers, cone beam computed tomography (CBCT) scans were performed, a 3D model generated, and pedicle screw insertions were planned. Seventy-eight insertions were performed. Technical accuracy was assessed on post-insertion CBCTs by measuring the distance between the navigated device and the corresponding pre-planned path as well as the angular deviations. Drilling and hammering into the pedicle were also compared. Navigation time was measured. An independent reviewer assessed a simulated clinical accuracy according to Gertzbein. Results: The technical accuracy was 1.7 ± 1.0 mm at the bone entry point and 2.0 ± 1.3 mm at the device tip. The angular deviation was 1.7 ± 1.7° in the axial and 1.6 ± 1.2° in the sagittal plane. Navigation time per insertion was 195 ± 93 seconds. There was no difference in accuracy between hammering and drilling into the pedicle. The clinical accuracy was 97.4% to 100% depending on the screw size considered for placement. No ionizing radiation was used during navigation. Conclusion: ARSN with instrument tracking for MISS is feasible, accurate, and radiation-free during navigation. Level of Evidence: 3 Abstract : In a cadaveric animal study for pedicle cannulation using augmented reality surgical navigation with instrument tracking, 78 insertions were performed. A technical accuracy of 1.7 ± 1.0 mm at bone entry, 2.0 ± 1.3 mm at device tip, and a clinical accuracy of 97.4% to 100% was achieved.